Crosslinked Spin-Assisted Layer-by-Layer Polyelectrolyte Nanofiltration Membrane: From Literature Review to Experiment - Farid Fadhillah (Indonesian Journal of Science and Technology, 2022)
Layer-by-Layer (LbL) assembly is considered as the most versatile and robust method in thin-film fabrication. However, its use in the preparation of desalination membrane is still in its infancy. Spin-assisted layer-by-layer assembly (SA-LbL), one of the LbL variants, was selected for the fabrication of a nanofiltration membrane due to its versatility to produce an ultra-thin film with highly controlled film properties within an incredibly short time. Branched-polyethyleneimine (PEI) and poly(sodium 4-styrenesulfonate) (PSS) were employed and alternately deposited on the top of the ultrafiltration polyethersulfone (PES) substrate. PEI/PSS film was then crosslinked using Gluteraldehyd (GA). The resulting membrane was tested at a feed concentration of 2000 ppm NaCl, a pressure of 10 bar, and a temperature of 25°C. Crosslinking time and many layers were varied to investigate the extent of crosslinking and its impact on membrane performance. The permeation test of (PEI/PSS)10 crosslinked for 6 hours showed rejection of 94.2 % and water flux of 4.2 L/h·m2 meanwhile uncrosslinked (PEI/PSS)35 showed rejection of 75.66% only. The result showed that crosslinking improved the rejection of NaCl with a smaller number of layers. This result also displayed SA-LbL method is promising and can be used to produce membrane suitable for NF or RO application.